(untitled) (مجلة جامعة سرت للعلوم الانسانية, 2024)
The research claims to demonstrate the importance of Schopenhauer’s pessimistic philosophy in relation to the other philosophers who were influenced by , and seek out the origin place of his ideas and philosophy, whether they were his personal life or his era in general. It also presents the logical sequence of his theory of pessimism, in which he started from idealism by making reality a mere reflection of thought. Both his thoughts and reality are subject to an absolute evil will, which makes the world a place of misery and life a journey of sadness and pain. There is no way to escape from this suffering, or at least alleviate it, except through a state of detachment and Sufism, which is the idea that he reached is blending the teachings of ancient Eastern religions - especially Buddhism - and Christianity.